Alginate Impression Material Reinforcement Using Polymethyl Methacrylate as Organic Filler - Paskatrianto, Ignatius Enrico; Takarini, Veni; Usri, Kosterman (European Journal of General Dentistry, 2025)
Dental alginate is one of the impression materials used in dentistry to reproduce intra- and extraoral structures. Alginate is a quite affordable and easy-to-use material, but because of its lower tear strength, it still has limitations in terms of accuracy. One way to increase the tear strength of alginate is by adding fillers. Polymethyl methacrylate (PMMA) is an example of an organic filler that can be utilized as an alternative reinforcement that could effectively increase dimensional stability. Thus, the purpose of this study was to evaluate the alginate's tear strength following the addition of PMMA as organic fillers.This experimental research consisted of four group samples. Sample A served as controls, while sample B included treated samples with varying PMMA additions of 3wt% (B1), 5wt% (B2), and 7wt% (B3). Each group had five samples. The tear strength test was conducted according to ISO Standard 21563:2021 using a Universal Testing Machine, which was followed by characterization using Scanning Electron Microscope (SEM) and Fourier Transform Infra-Red (FTIR) spectroscopy.The tear strength results were then evaluated by One-Way Analysis of Variance (ANOVA) following Tukey's test (p < 0.05).The tear strength of the control sample (A) was 0.540 N/mm. Meanwhile, the treated samples had tear strengths of 0.612 N/mm (B1), 0.663 N/mm (B2), and 0.596 N/mm (B3). There was a difference between the control and the treated samples that used PMMA fillers (p < 0.05). These results are supported by SEM and FTIR results related to physical closure or blocking of the alginate porous structure and the slight changes in its functional group.The addition of PMMA fillers to dental alginate provides reinforcement as the tear strength increases. This could impact the accuracy of the impression especially when the material is quickly removed from the oral structures. Additional investigation may assess the biocompatibility attributes further.
Keywords: dental alginate; polymethyl methacrylate filler; tear strength; reinforcement